Penerapan Model Pembelajaran Problem Solving pada Pembelajaran IPA Siswa Kelas IV SD - Chicha Apriyanti; Ek Lokaria; Nur Fitriyana (Journal of Elementary School (JOES), 2023)
This study aims to determine the completeness of science learning outcomes after the problem solving model is applied to fourth grade students at SD Negeri 40 Lubuklinggau. This research method is quasi-experimental with the Pretest and Posttest Group research design. The population is all student classes consisting of one class with a sample of 25 students. The data collection technique used a multiple choice test with 20 questions, the data analysis technique obtained using the z test obtained zcount = 3.21 and ztable = 1.71 then Ho was rejected and Ha was accepted. Based on the results of the research and discussion, it can be concluded that there is an influence of the Problem Solving learning model on the science learning outcomes of students at SD Negeri 40 Lubuklinggau Keywords: Learning Outcomes, Natural Science, and Problem Solving